Penguatan Pendidikan Karakter melalui Pembelajaran Pendidikan Agama Islam di SD Negeri 1 Gedung Sari - Putri, Kurnia Dwi; Rohmah, Arifiani Nailul Fauziyah; Syafitri, Meli; Anggraini, Soca (CV. Creative Tugu Pena, 2022)
The purpose of this study was to analyze the strengthening character education in islamic education of learning planning, strengthening character education in the implementation of islamic education learning and strengthening character education in the evaluation of Islamic Education learning at State of Elementary School 1 Gedung Sari. This research used descriptive qualitative. Data collection techniques used non-participant observation, in-depth interviews, and documentation. Data analysis was data collection, data reduction, data presentation, conclusion and verification. The results showed that the strengthening character education in Islamic Education learning planning at at State of Elementary School 1 Gedung Sari was integrated into the objectives, materials, methods, and learning activities designed in the syllabus and lesson plans containing religious, nationalist, independent, mutual cooperation, and values ??values. integrity. Second, strengthening character education in the implementation of elementary schoool learning at State of Elementary School 1 Gedung Sari is integrated into preliminary activities containing religious values. The core activities contain religious values, nationalism, independence, mutual cooperation, and integrity. And the closing activity contains integrity and religious values. Third, strengthening character education in the evaluation of islamic education learning at State of Elementary School 1 Gedung Sari was integrated into authentic assessments, namely the realm of attitude, knowledge, and skills, which contain religious, nationalist, independent, mutual cooperation, and integrity. The strengthening of character education in the implementation of islamic education learning was still weak due to the lack of planting exemplary methods from teacher Keywords: Strengthening Education Character, Learning Education Character, Islamic Education